Newly modified Stoppa approach for acetabular fractures - Liu, Yong (Springer-Verlag, 2013)
PURPOSE: We present our experience of using a newly modified Stoppa approach combined with a lateral approach to the iliac crest in patients with acetabular fractures in reference to fracture reduction and fixation, technical aspects, and the incidence of complications. METHODS: We used a consecutive group of 29 adult patients with acetabular fractures treated operatively with a newly modified Stoppa approach between 2009 and 2011. The newly modified Stoppa approach was performed to fix the acetabular fractures with main anterior displacement and the anterior and lateral parts of the pelvis. This approach was combined with a lateral approach on the iliac crest for fractures of the iliac wing. RESULTS: All the patients were followed up for at least 1.5 years. Of the 29 patients, ten anterior column, two associated both column, seven anterior column with posterior hemi-transverse, four transverse, and six T-type fractures. The average blood loss was 950 mL, and average operative time was 155 minutes. Anatomic or satisfactory reduction was achieved in 96 % of the acetabular fractures. Two patients had mild symptoms of the lateral femoral cutaneous nerve and improved within three months. CONCLUSIONS: The newly modified Stoppa approach provides excellent visualization to the anterior column, quadrilateral surface and permits good postoperative results for treatment of acetabular fractures. We considered this technique as a viable alternative for the ilioinguinal approach when exposure of the anterior acetabulum is needed.